EARLY METFORMIN TREATMENT IMPROVES GLUCOSE TOLERANCE IN OVERFED LACTATING RATS (Arquivos do Mudi, 2023)
Metformin is the most widely used drug for the treatment of type 2 diabetes and metabolicdiseases worldwide. Lactation is understood as a sensitive phase of development capable ofprogramming the metabolism for health or disease in adult life. The aim of this study was toverify whether treatment with metformin during lactation could attenuate the metabolicdysfunctions in Wistar rats induced obesity by overfeeding during lactation. At birth, alllitters were adjusted to 9 pups (NL) for each mother and divided into two experimentalgroups: NL: Normal Litter Saline, NL-M: Normal Litter Metformin. Small Litter (SL) litterswere reduced to 3 pups per mother on the third day of life and were divided into twoexperimental groups: SL: Small Litter Saline and SL-M: Small Litter Metformin. Salina (S)pups received 0.9% saline solution from the first to the twelfth day of life via intraperitonealinjection. The other group received metformin (M) (100mg/kg of body weight (bw)/day) inthe same period of life. Early metformin treatment decreased body weight gain (BW) andfood intake (FI) in SL-M rats at 90 days old. The increase in retroperitoneal, mesenteric andgonadal fat reserves in SL animals not treated with metformin was shown to be reduced intreated SL animals. The intravenous glucose tolerance test showed greater tolerance in SL-M.We conclude that early treatment with metformin prevented BW gain and visceral adiposityin adult rats, caused by overfeeding during lactation, as well as improved glucose tolerance, aparameter also altered in small litter animals.